Influência do tratamento culinário na concentração e biodisponibilidade in vitro de metais, não-metais e espécies de arsênio em frutos do mar - Schmidt, Lucas (2015)
Over the last decades a wide variety of analytical methods and bioavailability, interactions, metabolism and toxicity studies were performed in order to evaluate the risks associated with contamination of heavy metals in seafood. Furthermore, most of these studies were performed using raw samples, and the few studies involving the assessment of influence of culinary treatment on heavy metals behavior involve inaccurate interpretations regarding the contaminant behavior after the cooking process. According to these aspects the present study aims to evaluate the influence of culinary treatment over metals (Cd, Cr, Cu, Hg and Pb) and non-metals (As, Se, S and species of As) concentration and bioavailability (in vitro) of five seafood species (shark, shrimp, squid tube, oysters and scallops). Three cooking procedures (boiling, frying and sautéing) plus the uncooked sample were evaluated for each seafood species. In addition, the presence and absence of spices (garlic, salt and lemon juice) was evaluated for each treatment. All seasonings (garlic, salt and lemon juice) and cooking medium (water, oil and butter) involved during the culinary treatments were collected for further mass balance evaluation. After each culinary treatment the seafood samples were freeze-dried and grinded. Metals and non-metals determination was performed using a inductively coupled plasma triple-quadrupole mass spectrometry (ICP-QQQ). Parameters such as weight, sample size, cooking time and temperature were previously optimized and selected. Moreover, parameters such as mobile phase, extraction solution, stability, sample weight and recovery test (AsB, As(III), As(V), DMA and MMA) were evaluated for speciation method development. Arsenic species were identified and quantified by liquid chromatography coupled to inductively coupled plasma mass spectrometry (ICP-LC-QQQ). The methodology used to investigate the culinary treatments influence on heavy metal concentration in seafood was considered as suitable for the purpose of this work. In addition, the sampling step evaluation proved to be very important for this study. All samples presented significant loss of As (15 to 45%) after the boiling process. Moreover, significant losses were observed for Cd (37 to 53%) in scallops samples which have undergone the boiling, frying and sautéing process; and Hg losses (14 to 33%) in shark and shrimp samples which have undergone the boiling, frying and sautéing process. No influence was observed between the culinary treatments with and without spices (garlic, salt and lemon juice). Among the studied samples in this work, the blacktip shark (Carcharhinus limbatus) sample was the one with the highest As and Hg concentration, and both As and Hg presented concentrations of 280 and 245% higher than the maximum level recommended by ANVISA, respectively. Moreover, this sample had a molar ratio of Se/Hg < 1, presenting higher risks to consumer health. The As speciation analysis method presented a good robustness regarding to the extraction solution stability, sample weight and use of different matrices. The major As species found in all samples was AsB. The As species show a high stability regarding the cooking treatment and the bioavailability assay. The bioavailable rate (%) of As species related to the As species originally present in the raw sample showed a similar behavior. Additionally, Hg presented a significant change in bioavailability due to the influence of culinary treatment. However, the bioavailability of other analytes from cooked samples proved to be independent of the culinary treatment.